2005
DOI: 10.1093/schbul/sbj072
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Working Memory as a Cognitive Endophenotype of Schizophrenia: Assessing Risk for Pathophysiological Dysfunction

Abstract: Research suggests that first-degree relatives and individuals with schizophrenia spectrum personality disorders (SSPD) may represent nonpenetrant carriers of the genetic diathesis for schizophrenia. This study examined visuospatial working memory (SWM) as a cognitive endophenotype of schizophrenia by expanding the concept of risk for pathophysiological dysfunction beyond overt psychosis. Risk was thus defined by familial status and the presence or absence of SSPD. SWM was assessed in the following groups, in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 50 publications
3
43
0
Order By: Relevance
“…In humans, a previous study showed an association between NTSR1 gene polymorphisms and schizophrenia (Lee et al, 1999). This result indirectly supports a connection between the NTSR1 gene and WM because impaired WM has been found to be an important endophenotype of schizophrenia (Glahn et al, 2003;Saperstein et al, 2006). Several lines of evidence have shown an important role of the hippocampus in WM.…”
Section: Discussionsupporting
confidence: 72%
“…In humans, a previous study showed an association between NTSR1 gene polymorphisms and schizophrenia (Lee et al, 1999). This result indirectly supports a connection between the NTSR1 gene and WM because impaired WM has been found to be an important endophenotype of schizophrenia (Glahn et al, 2003;Saperstein et al, 2006). Several lines of evidence have shown an important role of the hippocampus in WM.…”
Section: Discussionsupporting
confidence: 72%
“…Although previous n-back studies in ARMS samples found no difference in task performance relative to controls or only a statistical trend in terms of accuracy and reaction time, 11,12 behavioural studies in larger samples have indicated clear neuropsychological deficits in high-risk populations, 45,46 including individuals at genetic risk for schizophrenia, 47 confirming that these deficits may be a cognitive marker of increased vulnerability to disease. This is in line with previous studies reporting working memory deficits in the early course of the illness 6 and with a recent metaanalysis demonstrating that the psychosis high-risk state is characterized by prominent impairments in working memory.…”
Section: Discussionmentioning
confidence: 82%
“…Prior studies of the relationship between WM and schizotypal features among unaffected relatives of schizophrenia probands have shown generally mixed results (e.g., (Conklin et al 2005;Delawalla 2006;Johnson et al 2003;Saperstein et al 2006), possibly reflecting differences in the schizotypy assessment instruments and WM tasks employed across studies. The current results suggest that the LNS Reordered impairments in the relatives reflect vulnerability to schizophrenia rather than the clinical or subclinical features of schizophrenia spectrum disorders assessed in this study.…”
Section: Discussionmentioning
confidence: 95%